Pediatric Emergency Medicine Simulation Curriculum: Seizure Scenario - Jennifer Reid; Kimberly Stone (Association of American Medical Colleges, 2014)
Abstract Pediatric seizures impact children worldwide. In developed countries, the prevalence of epilepsy is 4-8 per 1,000 children. Of all children, up to 5% will have a febrile seizure before reaching age 5. Pediatric seizures can consist of a number of different seizure types. For this scenario, the focus is on generalized pediatric seizures, which involve both hemispheres of the brain and result in impaired mental status and bilateral motor manifestations (tonic and clonic movements). Medical providers must recognize a generalized seizure early, when a pediatric patient is more likely to respond favorably to treatment. Medical providers must anticipate and treat the primary complication of respiratory insufficiency to prevent additional morbidity or mortality. The goal of this scenario is to provide the learner with an opportunity to manage a potentially life-threatening pediatric seizure, where the correct steps need to be taken in a limited period of time. This resource provides a comprehensive package to support instructors teaching pediatric seizure using a simulation-based modality. It includes background knowledge, presimulation preparation guidelines, a simulation scenario, tools to help evaluate team performance and guide debriefing, tools to elicit student feedback on the instructor's performance, and supplemental educational materials for instructors to provide to their students. We included extensive preparatory material, to help the instructor prepare the environment and learners. The debriefing tools have been tailored specifically for this scenario, with advice on how the instructor can modify them for learners with different levels of experience and opportunities for improvement. This resource will help support standardization of the teaching process, allowing simulation instructors maximize their impact. Over the past four years, we found that instructors are better able to anticipate and optimize discussion of debriefing points when utilizing this resource.